2014
DOI: 10.1016/j.rser.2014.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Policy and regulation for smart grids in the United Kingdom

Abstract: The UK has adopted legal obligations concerning climate change which will place increased stresses on the current 'traditional' model of centralised generation. This will include the stimulation of large volumes of intermittent generation, more distributed generation and larger and more variable loads at grid extremities, potentially including large volumes of electric vehicles and heat pumps. Smarter grids have been mooted as a major potential contributor to the decarbonisation of electricity, through facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Since January 2016, the French government has supported subsidies and approved trading electricity directly in the market, so that renewable energy companies can preserve the profitability of investment [57]. The United Kingdom introduced FITs with contracts for difference (CFD) as measures to elicit investment needed to replace old facilities and expand low-carbon energy sources [58]. The CFD is contracted between renewable energy companies and government-owned low-carbon contractors, and the companies receive the difference between the reference price and the strike price for 15 years [59].…”
Section: Discussionmentioning
confidence: 99%
“…Since January 2016, the French government has supported subsidies and approved trading electricity directly in the market, so that renewable energy companies can preserve the profitability of investment [57]. The United Kingdom introduced FITs with contracts for difference (CFD) as measures to elicit investment needed to replace old facilities and expand low-carbon energy sources [58]. The CFD is contracted between renewable energy companies and government-owned low-carbon contractors, and the companies receive the difference between the reference price and the strike price for 15 years [59].…”
Section: Discussionmentioning
confidence: 99%
“…IoE and smart grids would allow system operators to promptly react to peaks or failures in electric energy demand and also to forecast these issues well in advance and to adjust to these situations by optimizing energy generation from, say, RES, accordingly. All these would increase energy market efficiency and profitability [36][37][38][39]. In a way, it is quite similar to the so-called "cashless economy", when the Internet is used to optimize payments and money transfers, and banks, financial institutions, as well as government regulators have an instant snapshot of all of those activities and transactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our study demonstrates that the problem of incumbents' disincentives has undermined the effectiveness of the Chinese model. A growing body of literature and empirical data has suggested that innovation in regulatory frameworks can provide utilities with incentives to become distributed network operators for renewable sources (Connor et al, 2014;Mah et al, 2014). New York City, for example, has introduced earning adjustment mechanisms by providing utility incentives to achieve peak reductions, and facilitate interconnection of DE sources (Mitchell, 2016).…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%